2006
DOI: 10.1128/jcm.44.4.1376-1381.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Norovirus from Fecal Specimens by Real-Time Reverse Transcription-Loop-Mediated Isothermal Amplification Assay

Abstract: In this study, we developed a one-step, single-tube genogroup-specific reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay for the detection of norovirus (NoV) genomes targeting from the C terminus of the RNA-dependent RNA polymerase gene to the capsid N-terminal/shell domain region. This is the first report on the development of an RT-LAMP assay for the detection of NoV genomes. Because of the diversity of NoV genotypes, we used 9 and 13 specially designed primers containing mixed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 26 publications
1
65
0
2
Order By: Relevance
“…3A), which may be ascribed to the five mismatches between the FIP primer and the respective C. krusei target site. An alternative to circumvent this lower sensitivity could be to utilize degenerated primers or a mixture of primers, which has proved successful in other LAMP assays (10,38). We confirmed that the LAMP reaction proceeds without a previous thermal denaturation of the template DNA (30), making this technique really isothermal (Fig.…”
Section: Vol 46 2008 Identification Of Clinically Relevant Yeast Spsupporting
confidence: 51%
“…3A), which may be ascribed to the five mismatches between the FIP primer and the respective C. krusei target site. An alternative to circumvent this lower sensitivity could be to utilize degenerated primers or a mixture of primers, which has proved successful in other LAMP assays (10,38). We confirmed that the LAMP reaction proceeds without a previous thermal denaturation of the template DNA (30), making this technique really isothermal (Fig.…”
Section: Vol 46 2008 Identification Of Clinically Relevant Yeast Spsupporting
confidence: 51%
“…These specimens gave negative results in the sRT-LAMP assay within 90 min (data not shown). The specificity and selectivity of the RT-LAMP assay has also been demonstrated in previous studies (3,10,11).…”
mentioning
confidence: 87%
“…The sRT-LAMP assay was performed in 25 µl of reaction mixture with an RNA amplification kit (Eiken Chemical, Tochigi, Japan). The conditions for sRT-LAMP assay were the same as in the previous study (3), but the format of the reaction mixture was slightly changed. Briefly, 20 pmol of each of the three newlydesigned primers were added into the reaction mixture and seven forward loop primers were used as fluorescence-labeled primers.…”
mentioning
confidence: 99%
“…A study based on human volunteer showed the NoV infectious dose may be as low as 10to 100 viruses particles [6]emphasizes the need on highly sensitive method to detect their prevalence in water. NoV is usually detected in 3to 4h by RT-PCR method [22]. In latest innovation in DNA detection by amplification techniques, loop-mediated isothermal amplification (LAMP) has gain attention for it versatility in shorten the DNA amplification time to around one hour with results visible by naked eye using fluorescent dye.…”
Section: Discussionmentioning
confidence: 99%